Collagen hydrogels with controllable combined cues of elasticity and topography to regulate cellular processes. (11th June 2021) - Oyama, Tomoko G; Oyama, Kotaro; Kimura, Atsushi; Yoshida, Fumiya; Ishida, Ryo; Yamazaki, Masashi; Miyoshi, Hiromi; Taguchi, Mitsumasa
Abstract: The elasticity, topography, and chemical composition of cell culture substrates influence cell behavior. However, the cellular responses to in vivo extracellular matrix (ECM), a hydrogel of proteins (mainly collagen) and polysaccharides, remain unknown as there is no substrate that preserves the key features of native ECM. This study introduces novel collagen hydrogels that can combine elasticity, topography, and composition and reproduce the correlation between collagen concentration ( C ) and elastic modulus ( E ) in native ECM. A simple reagent-free method based on radiation-cross-linking altered ECM-derived collagen I and hydrolyzed collagen (gelatin or collagen peptide) solutions into hydrogels with tunable elastic moduli covering a broad range of soft tissues ( E = 1–236 kPa) originating from the final collagen density in the hydrogels ( C = 0.3%–14%) and precise microtopographies (⩾1 μm). The amino acid composition ratio was almost unchanged by this method, and the obtained collagen hydrogels maintained enzyme-mediated degradability. These collagen hydrogels enabled investigation of the responses of cell lines (fibroblasts, epithelial cells, and myoblasts) and primary cells (rat cardiomyocytes) to soft topographic cues such as those in vivo under the positive correlation between C and E . These cells adhered directly to the collagen hydrogels and chose to stay atop or spontaneously migrate into them depending on E, that is, the density of the collagen network, C . We revealed that the cell morphology and actin cytoskeleton organization conformed to the topographic cues, even when they are as soft as in vivo ECM. The stiffer microgrooves on collagen hydrogels aligned cells more effectively, except HeLa cells that underwent drastic changes in cell morphology. These collagen hydrogels may not only reduce in vivo and in vitro cell behavioral disparity but also facilitate artificial ECM design to control cell function and fate for applications in tissue engineering and regenerative medicine.